Hegel and Formal Idealism - Oza, Manish (Hegel bulletin, 2024)
I offer a new reconstruction of Hegel's criticism of Kant's idealism. Kant held that we impose categorial form on experience, while sensation provides its matter. Hegel argues that the matter we receive cannot guide our imposition of form on it. Contra recent interpretations, Hegel's argument does not depend on a conceptualist account of perception or a view of the categories as empirically conditioned. His objection is that, given Kant's dualistic metaphysics, the categories cannot have material conditions for correct application. This leads to subjectivism in the content of experience: the subject is given an implausibly strong role in determining what is the case. Hegel's own absolute idealism solves this problem.